Sacrococcygeal teratoma and normal alphafetoprotein concentration in amniotic fluid. Issue 5 (October 1985) - Szabó, M; Varga, P; Zalatnai, A; Hidvégi, J; Tóth, Z; Papp, Z
Abstract : It is usually assumed that in the case of sacrococcygeal teratoma the concentration of alphafetoprotein in the amniotic fluid is increased. In the case reported here the AFP concentration in the amniotic fluid was found to be normal in spite of a large teratoma not covered with skin. Possible reasons for this are discussed and the histological characteristics of the tumour are reported. It is emphasised that this teratoma could not have been recognised antenatally by normal AFP screening, but was only possible by ultrasound examination.